Enchanted by economics, culture, education, and language:Studies by Lívia Ablonczyné Mihályka on the occasion of her 70th birthday - Fejes-Nádai, Julianna (Tér - Gazdaság - Ember/Journal of Region, Economy and Society, 2024)
The title of this collection of studies reflects and encapsulates the decades-long academic career of Professor Lívia Ablonczyné Mihályka. The publication was released on the occasion of her 70th birthday as a token of recognition and respect for the professor’s educational and research work. The volume, published in 2023 by the Department of International Studies and Communication at Széchenyi István University (editors: Júlia Szőke, Petra Kecskés, Anikó Tompos) and published by Universitas-Győr Nonprofit Kft. in 2023, the diverse topics and useful research results presented in the volume provide insight into the social science research currently being conducted in higher education in the fields of economics, culture, and education. The authors of the English and Hungarian articles are researchers from Hungary and other countries, and this diversity is one of the great values of the volume.